THE RELATIONSHIP BETWEEN RISK FACTOR AND EARLY DETECTION OF BREAST CANCER AMONG FERTILE WOMEN - Kusumawati, Yuli; Miasari, Tutyan (Universitas Ahmad Dahlan, 2014)
Background: Breast cancer is the most common cancer in women, 10 % of all women in the world suffer from breast cancer in her life. The pathophysiology of breast cancer is very slow in dozens or even decades. However in theearly stage,breast cancer can be identified by early detection and treatment so that strived for cancer deaths are still preventable.Method: This study aimed to determine the relationship between family history, cigarette exposure, and the use of oral contraceptives and the action of early detection of breast cancer in fertile women ofThis study was an observational study used cross sectional design. The population was all women of childbearing age in Dawung Village Subdistrict Kebakkramat Karanganyar. Sample size was 88 taken by simple random sampling method. Data analysis was using the Fisher Exact test.Results: The results showed that there was no correlation between family history of breast cancer, use of oral contraceptives with early detection of breast cancer. While cigarette exposure showed correlation with early detection of breast cancer.Conclusion: It is recommended to women as well as their family to seek information regarding the risks and early detection of breast cancer. The detection can be done at least once in a month after menstruation,Â although it does not include high risk.Â Keywords: cancer history in family, cigarette exposure, oral contraception, early detection of breast cancer.